THE INFLUENCE OF INTERNAL CORPORATE COMMUNICATION ON BRAND COMMUNITY - Fortunisa, Ananda; Elsyah, Riska Dwinda (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2022)
Many companies implement brand community strategies to increase brand loyalty and brand engagement. Previous research on the brand community has focused more on the marketing aspect, with consumers as the target audience of the strategy. Many startup companies in Jakarta are adopting this strategy internally to increase employee engagement with the brand. This article further analyzes the brand community strategy in human resource management, which has been very little discussed by previous research. By hypothesizing that internal corporate communication is a factor that increases brand community strategy activities for employees, this study examined the relationship between internal corporate communication and brand community for millennial employees at digital startup companies in Jakarta. An online survey was conducted by distributing questionnaires to startup millennial employers and got 107 responses. SEM test analyzes the relationship between internal corporate communication (independent variable) and brand community (dependent variable). The dimensions used in this study's internal corporate communication variables refer to brand message effectiveness, brand feedback, and communication channels. In contrast, brand community variables' dimensions refer to the experience of information, socialization, human-machine interaction, and entertaining activity. This study's results indicate the company's internal communication management's strong influence on brand community activities. As novel insights, the results of this study are the first quantitative research to explain the relationship between internal corporate communication and the brand community, especially in the human resource management communications sphere. To cite this article (7th APA style): Fortunisa, A. & Elsyah, R. D.  (2022). The Influence of Internal Corporate Communication on Brand Community. Journal Communication Spectrum: Capturing New Perspectives in Communication, 12(1), 57-67. https://doi.org/10.36782/jcs.v12i1.2245